Use of an anti-low density lipoprotein receptor antibody to quantify the role of the LDL receptor in the removal of chylomicron remnants in the mouse in vivo. - Choi, S Y (1991)
Lipoproteins are removed from the plasma by LDL receptor-dependent and -independent pathways. The relative contribution of these has been established for LDL by using modified lipoproteins, but this has not been possible for apoE-rich lipoproteins, such as chylomicron remnants. To do this, we used a monospecific antibody to the rat LDL receptor. The antibody was injected intravenously into mice followed by 125I-lipoproteins. Blood samples were obtained sequentially and radioactivity measured to determine the plasma clearance of the lipoproteins. The animals were then sacrificed and the tissues removed, dried, and the radioactivity measured to determine tissue uptake. An albumin space was also measured to correct for blood trapping. With 125I-human LDL, approximately 50% of the injected dose was cleared in 180 min. This was reduced to 30% by the antibody and this was identical to the disappearance of reductively methylated LDL. This is a lower estimate of LDL-mediated uptake (40%) than in other species. LDL uptake per gram tissue was similar for the liver and the adrenal gland and was approximately 50% LDL receptor-dependent in both tissues. With 125I-chylomicron remnants, clearance was much more rapid with approximately 50% cleared in 5 min. By agarose gel electrophoresis, radioactivity was not transferred from chylomicron remnants to other lipoprotein classes. Chylomicron remnants with label on only apoB or in 3H-cholesterol esters showed a similar pattern. Combining the estimates of the three labeling procedures, approximately 35% of the 30 s and 25% of the 5 min chylomicron remnant disappearance was LDL receptor dependent. The liver, per gram tissue, took up five times as much radioactivity as the adrenal gland. At 5 min, at least 50% of this was LDL receptor-dependent in liver and 65% in adrenal gland. We conclude that the LDL receptor plays a major, and somewhat similar quantitative role in the clearance of both LDL and chylomicron remnants in the mouse. However, at least in the mouse, non-LDL receptor-mediated lipoprotein clearance is quantitatively important and is also very rapid for chylomicron remnants. Thus, for chylomicron remnants, it can easily compensate for LDL receptors if they are blocked or absent. Further, the tissue distribution of lipoprotein uptake may be directed by factors other than LDL receptor density.